A IGREJA METODISTA E SUA AÇÃO PASTORAL FRENTE AO FENÔMENO DO ENVELHECIMENTO POPULACIONAL BRASILEIRO - Nogueira, Paulo Dias (2009)
Population aging is of great concern worldwide. In Brazil, such phenomenon has brought new challenges to the government and to the society as a whole. The Methodist Church, as part of this society, holds a strong commitment to social issues with a Pastoral proposal entitled Plan for the Life and Mission of the Church (PLMC). Therefore, the aim of this study was to analyze the Pastoral action of the Methodist Church towards the Brazilian population aging phenomenon. This study included a historical method, according to Lakatos (1991), for the first and second chapters; and a statistical one for the third chapter. In the first chapter, the concepts and prejudices related to old age and aging were addressed, considering a demographic analysis of the Brazilian population aging as well as brief comments on the old age towards neoliberalism. The second chapter was aimed at a brief history and concept of relevant terms to research: Practical Theology, Pastoral, Praxis and Methodist Church. Finally, the third chapter involved an analysis and discussion of the results of field research conducted in three churches to assess what Pastoral action the Methodist Church has been taking towards the population aging phenomenon. The results of this study showed that the Methodist Church has been pastorally acting in an irrelevant manner towards this phenomenon, suggesting that further studies are needed to provide the elderly population with more information on aging using key Pastoral approaches.(AU)